A retained foreign body granuloma mimicking a left ventricular psuedoanuerysm. (2016) - Patrini, Davide; Gulamhussein, Mohamed Amirali; Pellegrino, Pasquale; Redaelli, Marianna; Pararajasingham, Jonathan; Lawrence, David; Panagiotopoulos, Nikolaos
Highlights: Retained foreign objects describes a mass composed of a central cotton core surrounded by foreign body reaction. It represents an unfortunate event for the patient and the surgeon with severe implications. This case highlights the important clinical history features for diagnosing this surgical error. Need for implementing definite strategies to avoid retained foreign objects in surgical practice. Abstract: Introduction: Gossypiboma, also referred to as a textiloma, gauzoma or muslinoma describe a mass in the body composed of a central cotton core surrounded by a foreign body reaction. It has an estimated incidence of 1/1000–1/10000 surgeries, occurring in the abdomen (56%), pelvis (18%) and least commonly the thorax (11%) and represents an unfortunate event for both the patient and the operating surgeon with severe liability implications. Presentation of case: We report a case of a 49-year-old male with Marfan Syndrome who was admitted to the cardiology department with a four day history of shortness of breath and associated dull, non-radiating chest pain. Past history included a previous Bentall procedure for a type-A aortic dissection and coronary artery bypass grafting involving a saphenous vein graft to the right coronary artery. A computed tomography (CT) scan showed a round, heterogeneous mass measuring 14 × 9 cm with lobulated contours, situated adjacent to the left ventricle along the left posterior region of the aorta. The mass was resected and further dissection revealed a plastic band harboured from the core of the mass. Discussion: The majority of cases of intrathoracic gossypiboma present as intractable cough or an incidental finding on radiological evaluation. Dyspnoea alone is relatively underreported as a presenting symptom of this condition Conclusion: This case highlights the important clinical history features for diagnosing this surgical error, including persistent respiratory symptoms and a history of cardio-thoracic surgery. It also emphasizes on the need for implementing definite strategies to prevent the occurrence of gossypiboma in surgical practice.